Intervention fidelity in a school-based diet and physical activity intervention in the UK: Active for Life Year 5. Issue 1 (December 2015) - Campbell, Rona; Rawlins, Emma; Wells, Sian; Kipping, Ruth; Chittleborough, Catherine; Peters, Tim; Lawlor, Debbie; Jago, Russell
Abstract Background Active for Life Year 5 (AFLY5) is an educational programme for Year 5 children (aged 9–10) designed to increase children's physical activity, decrease sedentary behaviour and increase fruit and vegetable intake. This paper reports findings from a process evaluation embedded within a randomised controlled trial evaluating the programme's effectiveness. It considers the fidelity of implementation of AFLY5 with a focus on three research questions:1. To what extent was the intervention delivered as planned? 2. In what ways, if any, did the teachers amend the programme? and 3. What were the reasons for any amendments? Methods Mixed methods were used including data collection via observation of the intervention delivery, questionnaire, teacher's intervention delivery log and semi-structured interviews with teachers and parents. Qualitative data were analysed thematically and quantitative data were summarised using descriptive statistics. Results Following training, 42 of the 43 intervention school teachers/teaching staff (98 %) were confident they could deliver the nutrition and physical activity lessons according to plan. The mean number of lessons taught was 12.3 (s.d. 3.7), equating to 77 % of the intervention. Reach was high with 95 % of children in intervention schools receiving lessons. A mean of 6.2 (s.d. 2.6) out of 10 homeworks were delivered. Median lesson preparation time was 10 min (IQR 10–20) and 28 % of lessons were reported as having been amended. Qualitative findings revealed that those who amended the lessons did so to differentiate for student ability, update them for use with new technologies and to enhance teacher and student engagement. Teachers endorsed the aims of the intervention, but some were frustrated with having to adapt the lesson materials. Teachers also a reported tendency to delegate the physical activity lessons to other staff not trained in the intervention. Conclusions Fidelity of intervention implementation was good but teachers' enthusiasm for the AFLY5 programme was mixed despite them believing that the messages behind the lessons were important. This may have meant that the intervention messages were not delivered as anticipated and explain why the intervention was found not to be effective. Trial registration ISRCTN50133740 .